Proprietary Income, Entrepreneurial Risk, and the Predictability of U.S. Stock Returns - Mathias Hoffmann (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2006)
Proprietors are an important group of stockholders and non-diversifiable entrepreneurial risk could therefore help explain time-varying risk premia on the aggregate stock market. This paper suggests an entrepreneurial distress factor that is highly correlated with the aggregate consumption-wealth ratio and that has considerable forecasting power for U.S. stock returns. I call this factor the cpy -residual because it can be be represented as a cointegrating relationship between consumption (c) and income from proprietary (p) and non-proprietary (y) wealth. My interpretation of cpy as an entrepreneurial risk factor is based on a number of empirical observations: first, cpy mainly reflects cyclical fluctuations in proprietary income and secondly it is highly correlated with cross-sectional measures of idiosyncratic entrepreneurial risk. Furthermore, and in line with the theoretical mechanism, its predictive power has started to decline since the beginning of the 1980s as stock market participation has widened with the advent of tax-deferable employer-sponsored pension plans and as proprietary income risk has become more easily diversifiable in the wake of state level bank deregulation.
Keywords: E31; G12; E21; 519; Non-insurable background risk; entrepreneurial income; equity risk premium; long-horizon predictability